Clinical characteristics and treatment outcomes of coats disease in a Saudi Arabian population - Al-Qahtani, Abdullah (2015)
Purpose: To present the clinical aspects and treatment outcomes of Coats disease in Saudi Arabia. Methods: A retrospective chart review was performed of 92 patients (97 eyes) diagnosed with Coats disease at King Khalid Eye Specialist Hospital from 1983 to 2010. Results: The most common presenting complaint was decreased visual acuity followed by strabismus and then leukocoria. Snellen visual acuity was 20/20 to 20/50 in 9 eyes (9%), 20/50 to 20/160 in 11 eyes (11%), 20/200-counting fingers in 29 eyes (30%), and hand motion to no light perception in 24 eyes (25%). Telangiectasia was located in the preequatorial area in 71 eyes (73%) and most commonly involved the temporal retina in 67 eyes (69%). In eyes with clear view to the fundus, quadrant involvement by telangiectasia had the following distribution: 1) quadrant (n = 36, 37%); 2) quadrants (n = 26, 27%); 3) quadrants (n = 8, 8%); and 4 quadrants (n = 15, 15%). Total retinal detachment was present at presentation in 28 eyes (29%) and neovascular glaucoma in 8 (8%). Based on the Shields classification, the eyes were Stage 1 (n = 1, 1%), Stage 2A (n = 7, 7%), Stage 2B (n = 23, 24%), Stage 3A1 (n = 26, 27%), Stage 3A2 (n = 12, 12%), Stage 3B (n = 16, 17%), Stage 4 (n = 11, 11%), and Stage 5 (n = 5, 1%). Stage 3A was the most commonly presented stage (39%). Primary management included cryotherapy (19%), laser photocoagulation (64%), intravitreal agents (9%), and surgical drainage (4%). Combination treatment was performed in 29% of eyes. Thirteen eyes (13%) were enucleated because of clinical suspicion of retinoblastoma or the presence of glaucoma. Factors that were associated with a poor visual outcome of 20/200 or worse included age less than 10 years (relative risk: 1.27), Stages 3 and 4 disease (relative risk: 1.40), presence of subretinal fluid in all 4 quadrants including the fovea (relative risk: 14.25), and initial visual acuity of 20/200 (relative risk: 6.72) or worse (P < 0.005 for all factors). Conclusion: Although rare, Coats disease is usually advanced at presentation and has a poor visual prognosis in the Saudi population, like in other populations. The findings of this study give validity and applicability to the Shields staging scheme, which we recommend using in clinical practice.